2004
DOI: 10.1002/pssc.200304401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of iron in face‐centered cubic 4d metals

Abstract: PACS 75.50.Bb The magnetic moments and hyperfine fields at iron sites embedded in Rh, Pd and Ag face centered cubic structures were calculated using the first principle discrete variational method (DVM) and the fullpotential linear-augment plane wave (FP-LAPW) method. In DVM the systems were represented by, clusters of atoms, while in FP-LAPW supercells were used. The objectives of this work are to compare and contrast results from the two different computational methods in addition to comparison to experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Based on the results of this test, we use the energy cutoff as 400 eV and k mesh equivalent to at least 16 × 16 × 16 divisions of the fcc and 20 × 20 × 20 divisions of the bcc cubic unit cells. In Appendix A, we compare our pseudopotential data with all-electron linearised augmented-plane wave (LAPW) and experimental data [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for pure iron and palladium as well as for some of their compounds.…”
Section: E Calculation Of Formation Energiesmentioning
confidence: 99%
“…Based on the results of this test, we use the energy cutoff as 400 eV and k mesh equivalent to at least 16 × 16 × 16 divisions of the fcc and 20 × 20 × 20 divisions of the bcc cubic unit cells. In Appendix A, we compare our pseudopotential data with all-electron linearised augmented-plane wave (LAPW) and experimental data [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] for pure iron and palladium as well as for some of their compounds.…”
Section: E Calculation Of Formation Energiesmentioning
confidence: 99%
“…The latter method is then used to study the electronic and magnetic properties of Fe clusters. It is found that the results of single impurities obtained using FP-LAPW method and DVM are fairly comparable except for Rh [17]. With respect to Fe relaxed clusters it is found that antiferromagnetic coupling between the central Fe atom in the cluster and its neighboring Fe atoms, starts when the number of its Fe nearest neighbors equals 12 for Fe in Rh, whereas it starts at 42 in Pd and 24 in Ag.…”
Section: Introductionmentioning
confidence: 76%